The Influence of Relative Humidity and Pollution on the Meteorological Optical Range During Rainy and Dry Months in Mexico City - Blanca Adilen Miranda-Claudes; Guillermo Montero-Martínez (Atmosphere, 2024)
The Meteorological Optical Range (MOR) is a measurement of atmospheric visibility. Visibility impairment has been linked to increased aerosol levels in the air. This study conducted statistical analyses using meteorological, air pollutant concentration, and MOR data collected in Mexico City from August 2014 to December 2015 to determine the factors contributing to haze occurrence (periods when MOR < 10,000 m), defined using a light scatter sensor (PWS100). The outcomes revealed seasonal patterns in PM2.5 and relative humidity (RH) for haze occurrence along the year. PM2.5 levels during hazy periods in the dry season were higher compared to the wet season, aligning with periods of poor air quality (PM2.5 > 45 μg/m3). Pollutant-to-CO ratios suggested that secondary aerosols’ production, led by SO2 conversion to sulfate particles, mainly impacts haze occurrence during the dry season. Meanwhile, during the rainy season, the PWS100 registered haze events even with PM2.5 values close to 15 μg/m3 (considered good air quality). The broadened distribution of extinction efficiency during the wet period and its correlation with RH suggest that aerosol water vapor uptake significantly impacts visibility during this season. Therefore, attributing poor visibility strictly to poor air quality may not be appropriate for all times and locations.